Thermal Deformation Analysis of Automotive Disc Brake Squeal - Hassan, Muhammad Zahir (2007)
Automotive disc brake squeal has been a major problem concern in warranty issue and challenging problem since 1930s. A variety of tools have been developed which includes both experimental and numerical modelling to tackle this problems. The current project was undertaken to develop a validated thermo-mechanical finite element model considering both the mechanical structural compliance and thermal effect towards the instability study of disc brake system. A new approach is proposed through an integrated study of non-linear contact pressure analysis and coupled thermal analysis followed by instability study using the complex eigenvalue analysis method. An experimental investigation will be used to validate the numerical modelling results according to industry standard SAE J2521 procedure. The parametric study on the geometrical effect and materials of brake components will determine brake squeal contribution factors and provide design modification guideline to reduce or eliminate squeal problems.